Analyzing the role of customers’ experiences and emotional responses in shaping Generation Z’s impulse buying behavior on Shopee video platform - Thi Thuy An Ngo; Hoang Lan Thanh Nguyen; Ho Truc Anh Mai; Hoang Phi Nguyen; Thi Huyen Tran Mai; Phuoc Long Hoang (PLoS ONE, 2025)
The swift growth of e-commerce has markedly changed how consumers shop, especially among Generation Z, which is called Digital Natives. This study examines how product presentation videos on the Shopee video platform influence impulse buying behaviors in this group, focusing on how internal stimuli, including entertainment experience (ET), educational experience (ED), escapist experience (ES), and esthetic experience (EH) influence online impulse buying (OIB) through the mediation of arousal (AR) and pleasure (PL). In addition, demographic factors, including age, gender, and income, are treated as control variables. This research adopts a quantitative methodology, and data was gathered using a Likert scale questionnaire and a non-probability sampling method, while the SmartPLS statistical tool was used to analyze the interactions of these stimuli and their effect on the impulse buying behavior of Generation Z on digital platforms. Research indicates that entertainment and recreational activities boost emotional engagement by eliciting arousal and pleasure. Educational experiences increase knowledge and also stimulate these feelings. Escapist activities provide temporary relief from daily stresses, increasing arousal, but can also highlight personal insecurities, possibly reducing pleasure. Esthetic experiences, subject to personal tastes, provoke emotional reactions that may vary in pleasure. For Generation Z, arousal and pleasure significantly influence impulsive buying decisions. The insights indicate that effectively managing internal factors can trigger emotions leading to impulsive purchases, offering strategic marketing tactics for optimizing e-commerce on platforms like Shopee video. This research advances the understanding of consumer behavior theories in the digital era, emphasizing the intricate roles of arousal and pleasure in online impulse buying.